Paparan Formalin Menghambat Proses Spermatogenesis pada Mencit - Sri Surya Heryani, Luh Gde; Werdi Susari, Ni Nyoman; Kardena, I Made; Dewi Indira Laksmi, Desak Nyoman (Jurnal Veteriner; Vol 12, No 3 (2011))
Formaldehyde is one of the exogenous free radicals. During formaldehyde exposure, there will be morefree radical or reactive oxygen compound formed through electron transport chain. Excessive reactiveoxygen compound triggers the process of lipid peroxide reaction in the membrane of spermatozoa cell. Theaims of this study were to find out that formaldehyde exposure caused abnormalities in the number of thenumber of spermatogonium type A, spermatogonium type Pachytene, 7th spermatid and 16th spermatid inspermatogenesis process.This study was experimentally and randomly pretested-posttested- with controlgroup design. The samples of this study were adult male mice strain Balb-C (age 2-3 months) with thefollowing criteria: body weight between 22-25 grams and healthy. Randomly, 48 mice were divided intothree groups, were control group, the first treatment group and the second treatment group. Prior to thetreatment, were taken a half from each group for the pre-test, by preparing microscopic preparation testicleand examination was performed to the total spermatogenic cells. The rests of the mice were used as posttestexamination after 35 days treatment. On the 36th day, all the rest mice were necropsied for microscopictesticle preparation. The result of this study showed that the formaldehyde exposure caused significantlydecrease in the number of spermatogenic cells (p<0,05), the average of type A spermatogonium cells atcontrol group, 1st treatment group and 2nd treatment group were 39,90±0,51; 20,42±0,72; 15,65±0,88respectively; spermatogonium type Pachytene were 48,47±1,28; 32,60±3,06; 23,14±3,16 respectively; 7thspermatid were 97,47±5,28; 39,98±4,28; 30,36±2,96 respectively and16th spermatid were 73,08±4,05;21,70±1,70; 16,38±1 respectively.It can be concluded that the formaldehyde exposure decreased the amountof spermatogenic cells. The result of this study is expected to be used as the baseline for further study inorder to measure formaldehyde content as a free radical in testicle .
Keywords: formaldehyde exposure, free radical, spermatogenesis.